2016
DOI: 10.4103/2211-4122.187948
|View full text |Cite
|
Sign up to set email alerts
|

Late echocardiographic study of aortic valve and aortic root after surgery for type a acute aortic dissection

Abstract: Objective:In case of concomitant aortic regurgitation (AR) valve, sparing operation is considered the first choice in selected patients. The aim of this retrospective clinical and echocardiographic study was to evaluate the long-term survival results of conservative approach and the determinants of recurrent AR.Methods:From 2000 to 2011, fifty patients (median: 63 years and interquartile range: 53–72) underwent an aortic valve-sparing procedure for acute aortic dissection, and discharged alive. The long-term c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…that AR at presentation was not a predictor of subsequent reintervention of the aortic valve or AR in a retrospective case series. 14,15 In contrast Pesotto et al 16 did find that moderate or severe AR at presentation was associated with an increased risk of moderate or severe AR during follow-up in patients undergoing aortic valve resuspension.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…that AR at presentation was not a predictor of subsequent reintervention of the aortic valve or AR in a retrospective case series. 14,15 In contrast Pesotto et al 16 did find that moderate or severe AR at presentation was associated with an increased risk of moderate or severe AR during follow-up in patients undergoing aortic valve resuspension.…”
Section: Discussionmentioning
confidence: 94%
“…Few studies have examined the performance of the native aortic valve following type A aortic dissection and in these there is a lack of consensus regarding the significance of AR at presentation. Molteni et al and Tang et al found that AR at presentation was not a predictor of subsequent reintervention of the aortic valve or AR in a retrospective case series 14,15 . In contrast Pesotto et al 16 did find that moderate or severe AR at presentation was associated with an increased risk of moderate or severe AR during follow‐up in patients undergoing aortic valve resuspension.…”
Section: Discussionmentioning
confidence: 96%